2012
DOI: 10.1007/s10162-012-0347-y
|View full text |Cite
|
Sign up to set email alerts
|

Perilymph Pharmacokinetics of Markers and Dexamethasone Applied and Sampled at the Lateral Semi-Circular Canal

Abstract: Perilymph pharmacokinetics was investigated by a novel approach, in which solutions containing drug or marker were injected from a pipette sealed into the perilymphatic space of the lateral semi-circular canal (LSCC). The cochlear aqueduct provides the outlet for fluid flow so this procedure allows almost the entire perilymph to be exchanged. After wait times of up to 4 h the injection pipette was removed and multiple, sequential samples of perilymph were collected from the LSCC. Fluid efflux at this site resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 42 publications
4
48
0
1
Order By: Relevance
“…Thus, the first two samples represented fluid from the inner ear, the first sample from the vestibular organs and the second from the cochlea, and the third and subsequent samples originated from the cerebrospinal fluid almost exclusively. Although this pattern of inner ear fluid flow was established in guinea pigs, the cochlear and vestibular anatomy of the mouse supports a similar interpretation (Salt and Stopp 1979;Salt et al 2012). …”
Section: Inner Ear Volumessupporting
confidence: 56%
See 1 more Smart Citation
“…Thus, the first two samples represented fluid from the inner ear, the first sample from the vestibular organs and the second from the cochlea, and the third and subsequent samples originated from the cerebrospinal fluid almost exclusively. Although this pattern of inner ear fluid flow was established in guinea pigs, the cochlear and vestibular anatomy of the mouse supports a similar interpretation (Salt and Stopp 1979;Salt et al 2012). …”
Section: Inner Ear Volumessupporting
confidence: 56%
“…The second sample that had a lower fluorescein percent than the first could be lower due to faster entry of fluorescein into scala vestibuli and the vestibule than into scala tympani. A lower concentration in scala tympani could also result from physiological entry of CSF into the basal turn of the mouse cochlea comparable to that found in guinea pig (Salt et al 2012). At present, the degree to which CSF enters the mouse cochlea under conditions where the otic capsule is not perforated is unknown.…”
Section: Differences In Fluorescein Content In Vestibular Versus Cochmentioning
confidence: 87%
“…Here, we focused on direct injections into perilymph but the same homeostatic processes will also influence drug levels with other delivery methods, such as intratympanic applications. When used with injection methods that maintain the ear in the physiologic, sealed state, FITC-dextran was found to be retained in perilymph better than other substances studied (Salt et al 2012). …”
Section: Discussionmentioning
confidence: 93%
“…As the pipette was sealed into the ear, the cochlear aqueduct acted as the outlet for volume flow as a number of marker studies have shown (Salt et al, 2012b, Salt et al 2015). The pressure increase in the cochlea during injection is estimated to be less than 2 mm Hg and control injections produced only slowly-occurring, small changes of AP threshold, unrelated to the pressure changes at the start and end of injection (Salt et al, 2012b). The injection results in flow through the LSCC, the vestibule, scala vestibuli and scala tympani, allowing almost the entire perilymphatic space to be filled with drug.…”
Section: Methodsmentioning
confidence: 99%